Employee Engagement Mediates The Effect of Work-Life Balance on Job Stress Among Employees of The Badung Regency Government Transportation Department - Kd Satria Danuarta; I Gusti Made Suwandana (Blantika: Multidisciplinary Journal, 2026)
This study, titled “Employee Engagement Mediates the Effect of Work-Life Balance on Job Stress Among Employees of the Badung Regency Government Transportation Department”, examines the high operational burden on field employees of the Badung Regency Government Transportation Office, which is not always directly proportional to increases in work stress. This condition indicates the presence of psychological factors that may explain the relationship between employees’ ability to maintain work-life balance and the pressure experienced in the workplace. Therefore, this study positions employee engagement as a mediating mechanism in the relationship between work-life balance and job stress. This study used a quantitative approach with an associative design and involved 68 respondents selected through saturated sampling. Data were collected using a questionnaire based on a Likert scale and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results show that work-life balance has a negative and significant effect on job stress and a positive and significant effect on employee engagement. Employee engagement also has a negative and significant effect on job stress and has been shown to partially mediate the relationship between work-life balance and job stress. These findings confirm that work-life balance functions as a personal resource that can enhance work engagement while reducing job stress. This research contributes to the development of the Job Demands–Resources (JD-R) model and provides practical implications for employee welfare management.